Social Marketing Strategy Through Digital Campaigns as an Effort to Reduce Plastic Waste in Kupang City - Maria Sisilia Lou Kelen; Taqwa Sultan; Margaretha Sartien Kabanga (STIE Amkop Makassar, 2026)
Through changing public perception in reducing the use of single-use plastics through the digital campaign